2015
DOI: 10.1001/jamapsychiatry.2014.2637
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Exposure vs Eye Movement Desensitization and Reprocessing vs Waiting List for Posttraumatic Stress Disorder in Patients With a Psychotic Disorder

Abstract: The efficacy of posttraumatic stress disorder (PTSD) treatments in psychosis has not been examined in a randomized clinical trial to our knowledge. Psychosis is an exclusion criterion in most PTSD trials. OBJECTIVE To examine the efficacy and safety of prolonged exposure (PE) therapy and eye movement desensitization and reprocessing (EMDR) therapy in patients with psychotic disorders and comorbid PTSD. DESIGN, SETTING, AND PARTICIPANTS A single-blind randomized clinical trial with 3 arms (N = 155), including P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
230
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 288 publications
(259 citation statements)
references
References 50 publications
(48 reference statements)
17
230
2
3
Order By: Relevance
“…These findings are consistent with the results of a secondary analysis of a treatment study of narrative exposure therapy (NET) and treatment as usual among severely traumatized asylum seekers and refugees, which showed that DS did not substantially moderate the treatment outcomes (Halvorsen, Stenmark, Neuner, & Nordahl, 2014). A recent study replicated these findings by generalizing the results to individuals with a severe psychiatric condition and performing a secondary analysis of a randomized clinical trial comparing prolonged exposure with EMDR therapy among PTSD patients with psychosis (van den Berg et al, 2015; van Minnen et al, 2016). Patients with and without DS showed a similar decrease in PTSD symptoms with large effect sizes observed in both groups.…”
Section: Introductionmentioning
confidence: 85%
“…These findings are consistent with the results of a secondary analysis of a treatment study of narrative exposure therapy (NET) and treatment as usual among severely traumatized asylum seekers and refugees, which showed that DS did not substantially moderate the treatment outcomes (Halvorsen, Stenmark, Neuner, & Nordahl, 2014). A recent study replicated these findings by generalizing the results to individuals with a severe psychiatric condition and performing a secondary analysis of a randomized clinical trial comparing prolonged exposure with EMDR therapy among PTSD patients with psychosis (van den Berg et al, 2015; van Minnen et al, 2016). Patients with and without DS showed a similar decrease in PTSD symptoms with large effect sizes observed in both groups.…”
Section: Introductionmentioning
confidence: 85%
“…
There is mounting support for the notion that also, individuals with severe, or "complex," forms of PTSD respond positively to TFTs and that neither trauma history, comorbidity, nor severe dissociative symptoms negatively affect clients' response to TFTs Foa, Zoellner, Feeny, Hembree, & Alvarez-Conrad, 2002;Hagenaars, van Minnen, & Hoogduin, 2010;Jerud, Pruitt, Zoellner, & Feeny, 2016;Olatunji, Cisler, & Tolin, 2010;van den Berg et al, 2015;van Minnen, Arntz, & Keijsers, 2002;van Minnen, Harned, Zoellner, & Mills, 2012; There is mounting evidence suggesting that by increasing the frequency of treatment sessions, posttraumatic stress disorder (PTSD) treatment outcomes significantly improve. As part of an ongoing research project, this study examined the safety and effectiveness of intensive eye movement desensitization and reprocessing (EMDR) therapy in a group of seven (four female) patients suffering from complex PTSD and multiple comorbidities resulting from childhood sexual abuse, physical abuse, and/or work and combatrelated trauma.
…”
mentioning
confidence: 99%
“…It has also been used in trauma-focused therapy trials for PTSD in psychosis (e.g. van den Berg et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Multifactorial models of the pathways from traumatic events to psychosis have been proposed, and psychological therapies for post-traumatic stress responses in psychosis show promise (Hardy, 2017; van den Berg et al, 2015). This work has led to calls for the routine screening of trauma and post-traumatic stress responses in clinical practice (NICE, 2014).…”
Section: Introductionmentioning
confidence: 99%